Developing an early childhood oral health impact–specific health‐state classification system for a new preference‐based instrument, the ECOHIS‐4D. Issue 3 (18th April 2021) - Kularatna, Sanjeewa; Amilani, Uttara; Senanayake, Sameera; Tonmukayakul, Utsana; Jamieson, Lisa; Arrow, Peter
Abstract: Objectives: Most of the paediatric quality‐of‐life instruments in oral health research are not preference‐based measures, thus cannot be used in economic evaluations. The Early Childhood Oral Health Impact Scale (ECOHIS) is one such instrument which assesses oral health impact on children's quality of life among three‐ to five‐year‐olds. With increasing demands for more resource allocation in oral health care, there is a need for an outcome metric which can be used as the outcome in economic evaluations. The aim of this study was to develop a preference‐based, health‐state classification system from the existing ECOHIS instrument. Methods: The 13‐item ECOHIS instrument was applied to the carers of 280 preschoolers who participated in a clinical trial in metropolitan Perth, Western Australia. Exploratory factor analysis was conducted to assess the dimensionality of the ECOHIS. Rasch analysis was used to eliminate and select items per determined dimensions and to reduce the number of response options for each item, because six levels were not amenable to valuation. The final classification system was determined through a combination of psychometric and expert advice. Results: Items loaded on to four dimensions with the factor analysis. Using Rasch analysis, three items were selected from the first dimension (child functional and psychological impact) and one item from the second dimension (child social interaction impact). None were selected from the third dimension (parental distress and family function impact) as it is not an appropriate proxy method of measuring the level of impact on a child. The final classification system has four dimensions with three levels in each, and so it has been named the ECOHIS‐4D. Conclusions: The ECOHIS‐4D classification system is a new preference‐based instrument derived from the existing ECOHIS instrument. Future valuation studies will develop a utility value set for the health states defined by this classification system, and this will guide economic evaluations related to oral health interventions.